Kaidah Rasm Utsmani dan korelasinya dengan qiroah sab’ah - Solihun Wildan; Indana Zulfa Muntafiah; Ratna Eka Septiana; Nur Wakhid (Al Irfani: Journal of Al Qur'anic and Tafsir, 2022)
The science of Rasm Al-Qur'an is the science that studies the writing of the mushat Al-Qur'an which is done in a special way, both in writing the pronunciations and the forms of letters used. The writer of the Qur'an at the time of the Prophet Muhammad SAW . It was carried out by his friends both in writing and in sequence with the aim of uniting the Muslims in one kind of mushab by uniforming the reading and unifying the Tertip arrangement of the verses. Thus, there is no difference in understanding between Mushab and other Mushab.